Utilization of personal health informatics through intermediary users - Katule, Ntwa (Department of Computer Science, 2019)
Personal informatics are important tools in health self-management as they support individuals to quantify and self-reflect on their lifestyle. Human-computer interaction researchers have devoted resources on studying how to design such tools. Various motivational strategies have been explored for their capabilities in improving user engagement. However, such strategies are developed with an assumption that the targeted consumer of information is the one directly manipulating user interfaces of the system that has information. This may not always be the case for users in developing regions. As a result, such systems may not scale well in contexts where a targeted consumer (beneficiary) may use technology through the facilitation of another person (intermediary) whom is responsible for manipulating user interfaces, because such facilitators are not recognized as part of the system, hence motivational strategies don't cater for them. In order to uncover design implications for intermediated technology use in the context of personal health informatics (PHI), the researcher started with the theoretical framing of the work followed by a contextual enquiry which led to development of mobile applications' prototypes for tracking nutrition and physical activity. Evaluation of the prototypes revealed that a familial relationship is a prerequisite for such an intervention. The most promising combination involves family members, possibly a child and a parent working together. The study used self-determination theory to understand how a collaborative gamified system can increase engagement. The result revealed that gamification as the source of a significant increase in perceived competence in intermediary users whom also tended to consider themselves as co-owners of the interaction experience. Therefore, gamification was found to be a catalyst for increasing collaboration between an intermediary and beneficiary user of technology, provided that the two users that formed a pair had a prior social relationship. In the absence of gamification, intermediary users tended to be less engaged in the intervention. The study highlights both the positive and negative aspects of gamification in promoting collaboration in intermediated use and its general implications in health settings. Design considerations required in order to improve the overall user experience of both users involved are proposed. In general, this work contributes to both theory and empirical validation of factors for, supporting proximate-enabled intermediated use of personal health informatics.